أثر الوعي بالتوجه الريادي على جودة العمليات في شركات الاتصالات الأردنية ذات النطاق الدولي - عزات الحلالمة, محمد; عباس الخفاجي, نعمة (Recherches économiques et managériales, 2018)
هدفت الدراسة إلى تحليل أثر الوعي بالتوجه الريادي بأبعاده ( الوعي بالتوجه الإبداعي، الوعي بالتوجه نحو المخاطرة، الوعي بالتوجه الاستباقي، الوعي بالتوجه العدائي التنافسي، الوعي بالتوجه الاستقلالي ) على جودة العمليات بأبعادها ( جودة القيادة، جودة الموارد البشرية، جودة خدمة الزبون، التخطيط الاستراتيجي للجودة، جودة العمليات، جودة التصميم ). أجريت الدراسة على شركات الاتصالات الأردنية ذات النطاق الدولي، وحصل التركيز على آراء (295) مديراً فيها . اعتمدت الاستبانة أداة لجمع البيانات التي تم تحليلها باستخدام برنامج SPSS لاستخراج الوسط الحسابي، والانحراف المعياري، والانحدار الخطي المتعدد . تضمنت الدراسة الاستنتاجات الآتية : تميز بمستوى وعي المديرين بأبعاد التوجه الريادي . تميز بمستوى اهتمام المديرين بجودة العمليات وأبعادها . ثبوت صلاحية أنموذج الانحدار الخطي المتعدد لقياس أثر الوعي بالتوجه الريادي على جودة العمليات بصورة إجمالية وجزئية . احتل الوعي بالتوجه الاستباقي والاستقلالي مرتبة الأولوية في تفسير مجالات جودة العمليات . وأوصت الدراسة العمل على استدامة وعي المديرين بالتوجه الريادي وجودة العمليات وفق نظرة تكاملية . الكلمات المفتاحية : التوجه الريادي، جودة العمليات . Abstract This research paper aimed at analyzing the impact of awareness towards Entrepreneurial Orientation in all its dimensions (awareness towards innovation, awareness towards risk, awareness towards the proactive approach, awareness towards competitive and hostile orientation, and awareness towards independent orientation) on the quality of operations in all its dimensions (leadership quality, human resource quality, customer service quality, strategic planning of quality, quality of operations and design quality). The study was conducted on operationsn in accordance with the integrated view. the Jordanian telecom Companies of International Scope. The focus was on the views of (295) managers. The questionnaire adopted tool to collect data the were analyzed using the (SPSS) Program to extract the arithmetic mean, the standard deviation and the multiple linear regression. This study included the following conclusions: 1- Excellence in the managers' awareness level of the Entrepreneurial Orientation. 2- Excellence in the managers' interest level of the quality of operations and its dimensions. 3- The consistency of tha validity of thr multiple linear regression to measure the impact of awareness towards Entrepreneurial Orientation on the quality of operations totally and partially. 4- The awareness of the independent and proactive orientation occupied a ptiority rank in interpreting the aspects of thec quality of operations. This research paper recommended working on the sustainability of the managers' awareness on the Entrepreneurial Orientation and the quality of Key words: Entrepreneurial Orientation, The quality of operations .